Correlation between specific IgM levels and percentage IgG-class antibody avidity to Toxoplasma gondii Correlação entre nveis de IgM específica e percentual de avidez de anticorpos da classe IgG ao Toxoplasma gondii - Marcel Leite; Sonia Siciliano; Lucia Silvieri A. Rocha; Teresa R. Justa; Katia Regina César; Celso F. H. Granato (Revista do Instituto de Medicina Tropical de São Paulo, 2008)
Toxoplasmosis is an usually asymptomatic worldwide disseminated infection. In its congenital presentation it may lead to abortion or fetal malformations. Antenatal evaluation is considered of paramount importance to identify seronegative women and allow for prophylaxis. Recent improvements in sensitivity of IgM tests has made IgM detection an extremely protracted acute phase marker, and IgG avidity evaluation test became necessary. Observation has shown that a correlation can be established between IgM levels and avidity percentages, suggesting that frequently the avidity test may not be necessary. In this study we analyzed Toxoplasma gondii IgM levels of 202 samples and their IgG avidity percentages, in order to define specific levels whose IgM quantification could by itself define serodiagnosis and therefore make the avidity evaluation unnecessary. We showed that for IgM levels bellow 2.0 and above 6.0 serodiagnosis of toxoplasmosis could be established without need of IgG avidity test. IgM levels between these two parameters are associated with varying avidity indexes highlighting the importance of its evaluation as a means to confirm toxoplasmosis. Following this demonstration it was possible to avoid the avidity test for 75% of the cases, to reduce the turnaround time and to reduce costs. A Toxoplasmose é uma infecção universal e usualmente assintomática. A forma congênita, entretanto, pode resultar em aborto ou mal formações. Testes sorológicos estão indicados em situações onde há suspeita clínica, e na triagem pré-natal, quando são extremamente importantes para rastrear a infecção e orientar a gestante. O aumento da sensibilidade das técnicas para detecção de IgM, tornou necessário o desenvolvimento de recursos, como a avidez de IgG, visando obter novo marcador de infecção aguda. Embora exista correlação entre níveis de IgM e grau de avidez de IgG, a maioria dos testes de avidez associa-se a níveis baixos de IgM, sugerindo que o teste de avidez não fosse necessário. Portanto, correlacionamos níveis de IgM ...